Improved diabetes control, allowing insulin cessation, after direct acting antiviral treatment (DAAT) of hepatitis C. Issue 4 (21st April 2022) - Surendran, Aarthi; Bhalla, Aditya; Whyte, Martin Brunel
Abstract : There is a bidirectional relationship between hepatitis C and type 2 diabetes. The risk for developing type 2 diabetes is increased in patients with chronic hepatitis C virus (HCV) infection—with the prevalence of diabetes ranging from 13% to 33%. This is likely underpinned by insulin resistance. Type 2 diabetes may also be a predisposing factor for HCV infection. The new non-interferon-based therapeutic regimens for hepatitis C have transformed care and can eradicate disease. In this report, we show how such a regimen eradicated viral load, improved hepatocellular blood markers and significantly improved dysglycaemia, such that all glucose-lowering medication could be stopped.